PENGARUH KONVERGENSI IFRS, PREDIKSI KEBANGKRUTAN, KOMITE AUDIT, KOMISARIS INDEPENDEN DAN KUALITAS AUDIT TERHADAP TIMELINES PERUSAHAAN TAMBANG - Ariani Palupi; Suratno Suratno; Amilin Amilin (Universitas Pakuan, 2017)
ABSTRACT This study aims to investigate the effects of IFRS convergence, bankruptcy prediction, audit committee, independent commissioner, and quality audit on timelines. The samples used in this study are 25 mining companies listed on the Indonesia Stock Exchange Year 2012-2015 which obtained in accordance with certain criteria. This research uses secondary data which applied regression model of panel data (pooled data) using statistical tools Eviews. From the result of hypothesis tests by using panel data regression analysis, it can be concluded that: bankruptcy predictions and independent commissioner have a significant impact on timelines, while IFRS convergence, audit committee and audit quality has no significant effect on timelines. Keywords: Timelines, IFRS Convergence, Bankruptcy Prediction, Audit Committee, Independent Commissioner, Quality Audit